Analgesic efficacy of erector spinae plane block versus transversus abdominis plane block for laparoscopic cholecystectomy: a systematic review and meta-analysis of randomized controlled trial - Zewdu, Dereje; Tantu, Temesgen; Eanga, Shamil; Tilahun, Tamiru (Frontiers in Medicine, 2024)
Background: Although laparoscopic cholecystectomy (LC) is a minimally invasive surgery, it can cause moderate to severe postoperative pain. Erector spinae plane (ESP) and transversus abdominis plane (TAP) blocks are considered effective means for pain management in such cases; however, there is inconclusive evidence regarding their analgesic efficacy. This meta-analysis aimed to compare the efficacy of ESP block and TAP block for pain control in LC. We systematically searched Medline, PubMed, Scopus, Embase, and Google Scholar until January 26, 2024. All randomized clinical trials compared the efficacy of erector spinae plane block (ESPB) and transversus abdominis plane block (TAPB) for postoperative pain relief after LC. The primary outcomes were pain score at rest and on movement during the 1, 2, 6, 12, and 24 postoperative hours. The secondary outcome measurements consist of the total opioid consumption, first analgesia request time, and rates of postoperative nausea and vomiting. We analyzed all data using RevMan 5.4. Eight RCTs, involving 542 patients (271 in the ESPB group and 271 in the TAPB group), were included in the analysis. ESP block demonstrated statistically significant lower pain scores at rest and on movement than the TAP block at all-time points except at the first and sixth hours on movement postoperatively; however, these differences were not considered clinically significant. Additionally, patients who received the ESP block required less morphine and had a longer time before requesting their first dose of analgesia. There were no significant differences in postoperative nausea and vomiting incidence between the two groups. There is moderate evidence to suggest that the ESP block is effective in reducing pain severity, morphine equivalent consumption, and the time before the first analgesia request when compared to the TAP block during the early postoperative period in patients undergoing LC.